Relationship between Thermal Conductivity and Compressive Strength of Insulation Concrete: A Review - Wu, Chao; Liu, Shaoqing; Guo, Jianping; Ma, Hongqiang; He, Li (Journal of Research Updates in Polymer Science, 2023)
Developing insulation concrete with high strength is essential for the construction of energy saving buildings. This is important to achieve carbon neutrality in the modern building industry. This paper reviews the existing studies in the literature on insulation concrete. This paper aims to reveal the correlation between the thermal conductivity and strength of concrete and identify the most effective method to make insulation concrete with lower thermal conductivity but higher strength. The review is carried out from two perspectives, including the effects of different foaming methods and various lightweight aggregates. As for the foaming methods, the chemical and mechanical foaming methods are discussed. As for the lightweight aggregates, cenospheres, porous aggregates, aerogels, and phase change materials are assessed. It is clearly observed that the thermal conductivity and compressive strength of concrete can be fitted by a linear function. As for the foaming methods, chemical foaming using hydrogen peroxide is the most effective to produce concrete with relatively lower thermal conductivity and higher compressive strength. For concrete with lightweight aggregates, cenospheres are the best option. Finally, recommendations are made to develop concrete with lower thermal conductivity and higher strength.